Treatment paths for localised prostate cancer in Italy: The results of a multidisciplinary, observational, prospective study (Pros-IT CNR). - Michela Buglione; Marianna Noale; Alessio Bruni; Alessandro Antonelli; Filippo Bertoni; Renzo Corvo'; Umberto Ricardi; Paolo Borghetti; Marta Maddalo; Claudio Simeone; Ercole Mazzeo; Angelo Porreca; et al. (PLoS ONE, 2019)
BACKGROUND:There are several treatments available to newly diagnosed prostate cancer (PCA) patients. Although surgery and radiotherapy (RT) with or without androgen deprivation therapy (ADT) are widely adopted treatment options for localized PCA together with active surveillance (AS), there is no consensus nor randomised trials on treatment selection, prospective quality of life (QOL), along with toxicity outcomes and according to treatment modality in the Italian population. The current study aimed to describe clinical-therapeutic features and QOL at PCA diagnosis, according to different treatment patterns in a large prospective, Italian population, enrolled in the Pros-IT CNR study. METHODS:The Pros-IT CNR is an on-going national, multicenter, observational, prospective study on patients affected by PCA who have been referred by 97 Italian Urology, Radiation Oncology and Medical Oncology facilities participating in the project. The possible relationships between the treatment patterns reported in the 6 month follow-up case report form and patients' features at diagnosis were evaluated using exploratory multiple correspondence analysis (MCA) and other data analysis method. RESULTS:At diagnosis, surgery and AS patients were significantly younger, had fewer comorbidities, lower PSA levels and Gleason Score (GS) values; they were also diagnosed at an earlier stage of disease with respect to the RT or ADT patients who showed significantly worse QoL scores at the time of diagnosis. CONCLUSIONS:An analysis of the data collected at baseline and 6 months later uncovered substantial differences in ages, comorbidities, clinical and QOL features in the various treatment groups. These findings do not fully reflect the current PCA treatment guidelines and suggest the need for a multidisciplinary consensus guideline to ameliorate both the counselling and treatments of PCA patients.